The Implementation of Task Based Learning in Teaching Writing Descriptive Text to The Junior High School - Achmad Saifudin; Slamet Setiawan; Syafi’ul Anam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The research aims at investigating the implementation of task based learning conducted by the teacher in teaching writing descriptive text for junior high shool students of seven grade.The student still have problem in writing especially descriptive text. The study examine show to the teacher conducs the task based learning in teaching writing trought some step and elaborates students’ ability in writing descriptive text.the research used qualitative approach because the result of the data analyzed was in descriptive phenomenom such a word, sentence and utterence. The data is collected from observation, interview and students’ writing. The analysis of the data was conducted thought categorization, data display and drawing conclusion. The subjects of this research are an english teacher and his students of VII grade. The result of the study indicates that the implementation of task based has many weaknesses in some aspects.The consuming time in doing the task is one of the matters. Students’ use of mother tongue instead of the target language makes the implementation of task based learning does not go as expected.In reference to the findings of the study, some suggestion proposed. The english teacher should use and design task which will not consume more time,so the step in task based learning will bwe accommodated in a meeting. The student should speak in the target language and the task based learning is implemented in order to reach the aim of this approach. Key Words : Task – Based Learning, Descriptive text, Students’ writing